SECURITY MANAGEMENT PLAN FOR INFORMATION ASSETS OF OBJECTS OF THE AVIATION TRANSPORT COMPLEX OF UKRAINE - Shulha, Volodymyr; Mishchenko, Andrii; Morklyanyk, Bohdan; Lazarenko, Serhii; Lishchynovska, Natalia (Ukrainian Information Security Research Journal, 2023)
Governing documents International Civil Aviation Organization (ICAO) define a safety management system as an element of corporate governance responsibility that defines a company's safety policy and its intentions to manage safety as an integral part of its overall business. Thus, the security management system (Security Management System, SeMS) is a part of the overall information asset management system of the aviation enterprise, which is based on risk analysis and is intended for the design, implementation, control, monitoring and improvement of measures in the field of information security. This system consists of organizational structures, policies, planning actions, responsibilities and procedures, processes and resources, and much more. An analysis of modern management measures of the information security system of air transport facilities based on international standards of the ISO series was carried out. A scenario for the implementation of the plan for managing the security of information assets of the air transport complex is proposed, which is based on the best experience of foreign countries.